2013
DOI: 10.1016/j.red.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Leveraged borrowing and boom–bust cycles

Abstract: Investment booms and asset "bubbles" are often the consequence of heavily leveraged borrowing and speculations of persistent growth in asset demand. We show theoretically that dynamic interactions between elastic credit supply (due to leveraged borrowing) and persistent credit demand (due to consumption habit) can generate a multiplier-accelerator mechanism that transforms a one-time productivity or …nancial shock into large and long-lasting boom-bust cycles. The predictions are consistent with the basic featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This paper contributes to the literature on open‐economy extensions of the seminal analysis in Kiyotaki and Moore (); see also Iacoviello (), Pintus and Wen (), Liu et al . (), and Pintus et al .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…This paper contributes to the literature on open‐economy extensions of the seminal analysis in Kiyotaki and Moore (); see also Iacoviello (), Pintus and Wen (), Liu et al . (), and Pintus et al .…”
Section: Introductionmentioning
confidence: 72%
“…This is because an expansion in the home economy due to, say, an increase in productivity, raises the world interest rate, which in turn hurts the foreign economy. Kiyotaki and Moore (1997); see also Iacoviello (2005), Pintus and Wen (2013), Liu et al (2013), andPintus et al (2016). In particular, we extend the small-open-economy settings of, among others, Kocherlakota (2000), Pintus and Wen (2013), and Kaas et al (2016) by considering a two-country model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jermann andQuadrini (2012) found that a financial shock that affects firms' borrowing ability has a large impact on employment and aggregate output. Pintus and Wen (2010) argued that interactions between habit persistence and credit constraints help propagate business cycle shocks. Del Negro, Eggertsson, Ferrero, and Kiyotaki (2010) introduced nominal rigidities into the model of Kiyotaki and Moore (2008) to examine the effectiveness of unconventional monetary policy.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature on finance and economic growth, Galor and Zeira (1993) and Aghion, Howitt, and Mayer-Foulkes (2005), among others, theoretically demonstrate that relaxing financial frictions promotes economic growth. In the literature on business cycles and financial frictions, Bernanke and Gertler (1989), Kiyotaki and Moore (1997), Cordoba and Ripoll (2004), and Pintus and Wen (2013) study the financial accelerator mechanism and investigate how and how much the researchers, however, few studies have conducted statistical testing to determine whether macroeconomic models with financial frictions can actually be applied to real economies. 2 In this paper, by developing a small open economy version of Kiyotaki and Moore's (1997) model following Kasa (1998), we derive a closed-form solution for the current account dynamics.…”
mentioning
confidence: 99%